2022
DOI: 10.3390/ijerph19063203
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Digital Technique to Analyze the Wear of CM-Wire NiTi Alloy Endodontic Reciprocating Files: An In Vitro Study

Abstract: The present study seeks to describe a novel digital measurement technique for analyzing the wear volume of controlled memory (CM)-wire NiTi alloy endodontic reciprocating files after clinical use. Material and Methods: Ten CM-wire NiTi endodontic reciprocating files were randomly used in ten first upper molar teeth within four root canals. The CM-wire NiTi alloy endodontic reciprocating files were subjected to preoperative and postoperative micro-computed tomography (micro-CT) scans to obtain accurate digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, most studies assessing instrument design have relied on information provided by manufacturers or the analyzing cross-sections and surface features [ 11 ], using stereomicroscopy [ 10 ] or scanning electron microscopy (SEM) [ 11 ]. More recently, attempts have been made to create 3D models of NiTi instruments using the non-destructive micro-CT technology [ 12 , 13 ]. However, these studies have shown that virtual models produced exhibit significant changes in design, including severely flattened cutting blades and deformations in the geometry of their tips.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies assessing instrument design have relied on information provided by manufacturers or the analyzing cross-sections and surface features [ 11 ], using stereomicroscopy [ 10 ] or scanning electron microscopy (SEM) [ 11 ]. More recently, attempts have been made to create 3D models of NiTi instruments using the non-destructive micro-CT technology [ 12 , 13 ]. However, these studies have shown that virtual models produced exhibit significant changes in design, including severely flattened cutting blades and deformations in the geometry of their tips.…”
Section: Introductionmentioning
confidence: 99%
“…However, an analysis conducted at a specific surface level may not be consistent across all the specimens, and the destructive nature of this approach may restrict a comprehensive evaluation of the entire instrument length. To address this limitation, the use of non-destructive imaging systems, including micro-CT (Faus-Matoses et al, 2022) has been proposed. Nevertheless, it is widely recognized that X-ray-based scanners have inherent limitations when imaging materials with high density and atomic weight, such as metals.…”
Section: Discussionmentioning
confidence: 99%
“…A similar methodology was previously used by Fraguas de San José et al to analyze the wear of dental implant drills after clinical use [ 14 ], Alakabani et al to analyze the removal capability of carrier-based root canal filling material from straight root canal systems [ 15 ], and Faus-Matoses et al to analyze the wear of CM-Wire NiTi alloy endodontic reciprocating files after root canal treatment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%